Efficacy and Safety of Capecitabine for Triple-Negative Breast Cancer: A Meta-Analysis - Xun, Xueqiong; Cao, Qinguang; Hong, Pan; Rai, Saroj; Zhou, Yeming; Liu, Ruikang; Hu, Huiyong (Frontiers in Oncology, 2022)
Background: Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer with limited treatment options and poor prognosis. Capecitabine as novel adjuvant chemotherapy for TNBCs remains controversial. Therefore, we conducted this meta-analysis to assess the efficacy and safety of capecitabine for early-stage TNBCs combined with Neo/adjuvant chemotherapy. Methods: We searched Medline, Embase, Web of Science and Cochrane databases updated on Mar 18, 2022 for relevant RCTs. In all, 11 RCTs with 5175 patients were included. We used hazard ratios (HRs) and odds ratios (ORs) to assess the differences between Disease-free survival (DFS), overall survival (OS) and adverse events. Results: Our study demonstrated significance differences in both DFS and OS (DFS: HR=0.77, 95% CI 0.68 to 0.86; OS: HR=0.73, 95% CI 0.63 to 0.85). In subgroup analysis, lower dosage group showed higher DFS (HR=0.79, 95%CI 0.69 to 0.91), higher frequency (HR=0.72, 95%CI 0.62 to 0.83) and adjuvant chemotherapy (HR=0.74, 95%CI 0.65 to 0.84). However, capecitabine was also associated with a higher risk of diarrhea (OR=3.10, 95% CI 2.32 to 4.15), hand-foot syndrome (OR=25.79, 95% CI 15.32 to 43.42) and leukopenia (OR=2.08, 95% CI 1.13 to 3.84). Conclusion: The addition of capecitabine to early-stage TNBC patients receiving standard adjuvant chemotherapy showed significant DFS and OS improvement with tolerable adverse events. The lower dosage and higher frequency of capecitabine combined with adjuvant chemotherapy demonstrated a better survival outcome.